Penerapan Fungsi Yudisial Peradilan Tata Usaha Negara terhadap Keabsahan Hasil Pilkades E-Voting: Studi Putusan PTUN Surabaya Nomor 31/G/2024/PTUN.SBY - Isna Mufida (Uniku Law Review, 2025)
This study examines the role of the State Administrative Court (PTUN) as a judicial control mechanism for the State Administrative Decree (KTUN) issued by the Regent of Magetan, particularly regarding the ratification and appointment of Village Heads elected through the E-voting system. Technological innovation in the Village Head Election in Magetan Regency, which should have increased efficiency and accountability, instead triggered disputes due to unresolved technical "irregularities and problems", resulting in the Surabaya PTUN Decision Number 31/G/2024/PTUN.SBY. Through normative legal research with a law-in-books approach, the analysis was conducted using Lawrence M. Friedman's legal system theory. The results of the study show that, in terms of Legal Structure, the lawsuit to the PTUN proves its function as a corrective institution against executive discretion. In terms of Legal Substance, this dispute tests the legality of the Regent's KTUN against the principles of LUBER JURDIL and the General Principles of Good Governance (AUPB), especially the principles of accuracy and professionalism. The systematic failure of e-voting has the potential to create procedural and substantive flaws, making the State Administrative Court (KTUN) inconsistent with substantive law and the AUPB. From a legal cultural perspective, the lawsuit by the losing candidate demonstrates the public's high level of legal awareness in demanding a clean democratic process. Regional governments are obligated to improve e-voting regulations and system quality.